Polyoxometalates as Heterogeneous Catalysts for Organic Reactions - Rafiee, Ezzat; Eavani, Sara (Current Organic Chemistry, 2017)
Over the past decade, polyoxometalates (POMs) have attracted extensive attention as homogeneous and heterogeneous catalysts or nanocatalysts for organic transformation. The most advantageous feature of POMs is the possibility of the catalyst design at atomic/molecular levels. They could be designed as multifunctional catalysts, based on different metal atoms or heteroatoms in their structure, counter cations, second structures, and etc. There are different ways for heterogenization of POMs for catalytic applications in literature. Two major groups have been reported for this purpose: exchanging the heteropoly acid (HPAs) protons with cations and immobilization of HPAs on a suitable solid support. The obtained heterogeneous catalysts have special properties and could be used in the wide range of organic reactions. Recent developments in this emerging area are discussed in this review, covering a little discussion about why the POMs are active catalysts. Then different POMcatalyzed organic reactions including oxidation, reduction, multicomponent, esterification and transesterification, C-C coupling, isomerization reactions, etc. were illustrated. According to the multifunctionality of the POM-base catalysts, this review compiles the recent advances (focusing on the period 2000-2016) in POM-catalyzed reactions which have attracted the interest of the scientific community addressing on development of environmentally benign synthetic processes.
Keywords: Heteropoly acids